Water-Soluble Coenzyme Q10 Inhibits Nuclear Translocation of Apoptosis Inducing Factor and Cell Death Caused by Mitochondrial Complex I Inhibition - Li, Haining (MDPI, 2014)
The objectives of the study were to explore the mechanism of rotenone-induced cell damage and to examine the protective effects of water-soluble Coenzyme Q10 (CoQ10) on the toxic effects of rotenone. Murine hippocampal HT22 cells were cultured with mitochondrial complex I inhibitor rotenone. Water-soluble CoQ10 was added to the culture media 3 h prior to the rotenone incubation. Cell viability was determined by alamar blue, reactive oxygen species (ROS) production by dihydroethidine (DHE) and mitochondrial membrane potential by tetramethyl rhodamine methyl ester (TMRM). Cytochrome c, caspase-9 and apoptosis-inducing factor (AIF) were measured using Western blotting after 24 h rotenone incubation. Rotenone caused more than 50% of cell death, increased ROS production, AIF nuclear translocation and reduction in mitochondrial membrane potential, but failed to cause mitochondrial cytochrome c release and caspase-9 activation. Pretreatment with water-soluble CoQ10 enhanced cell viability, decreased ROS production, maintained mitochondrial membrane potential and prevented AIF nuclear translocation. The results suggest that rotenone activates a mitochondria-initiated, caspase-independent cell death pathway. Water-soluble CoQ10 reduces ROS accumulation, prevents the fall of mitochondrial membrane potential, and inhibits AIF translocation and subsequent cell death.